Reduced Fluence Photodynamic Treatment for a Case of Chronic Central Serous Chorioretinopathy ? A Case Report - Tehmina Jahangir, Qasim Lateef Ch (Pakistan Journal of Ophthalmology, 2018)
To report a case of a 49 year old male with right sided recurrent chronic Central Serous Chorioretinopathy (CSCR). He was treated with half fluence Photodynamic Therapy resulting in resolution of CSCR and significant improvement in best corrected visual acuity. Chronic central serous chorioretinopathy (CSC) is a well-recognized entity characterized by accumulation of serous sub retinal fluid (SRF) which induces a localized detachment of the neurosensory retina. Patients can present with various visual complaints including central scotoma, metamorphopsia and micropsia. It is most frequently unilateral and affects young adult males more commonly. There is often a history of recent stress and the subject usually has a type A personality. The visual deterioration in chronic cases results from damage to the underlying retinal pigment epithelium (RPE) and photoreceptors. The underlying pathogenesis involves multifocal areas of choroidal vascular hyper permeability1,2. It is speculated that the fundamental mode of action of photodynamic therapy (PDT) with vertepor?n (Visudyne; Novartis Pharma AG, Switzerland) utilized for the treatment of CSC is the shutdown of the vessels in the choriocapillaris resulting in hypo-perfusion and extended remodeling of choroidal vasculature. We approached this case of chronic symptomatic CSC by treating him with half-?uence rate (25 J/cm2), without modifying the dose of vertepor?n (6 mg/m 2). The choice of a suitable ?uence rate enables one to evade indirect damage to surrounding structures such as RPE atrophy, ischemia of the choroid, and development of secondary choroidal neovascularization (CNV) because of less choriocapillaris damage3. The intervention was done after seeking permission from the hospital?s ethical and research committee. The author has no financial interest in the products used. The authors declare no conflict of interest. Keywords: Central serous chorioretinopathy, Photodynamic Therapy, Optical Coherence Tomography.